2006
DOI: 10.1002/zamm.200410226
|View full text |Cite
|
Sign up to set email alerts
|

On isotropic extension of anisotropic constitutive functions via structural tensors

Abstract: Key words anisotropic materials, isotropic functions, structural tensors MSC (2000) 15A72, 74E10We demonstrate that any number of vectors and second order tensors can merely characterize and represent one of the cylindrical groups and the triclinic, monoclinic, rhombic crystal classes. This suggests that, for anisotropic functions relative to any anisotropic material symmetry group other than those just mentioned, the widely used isotropic extension method via structural tensors has to result in isotropic exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Besides transverse isotropy and orthotropy, Liu’s list includes groups pertaining to crystal classes in the triclinic, monoclinic, and rhombic systems. More recently, Xiao et al [9] demonstrated that “any number of vectors and second order tensors can merely characterize and represent one of the cylindrical groups and the triclinic, monoclinic, rhombic crystal classes.” They proceed to assert what follows:This suggests that, for anisotropic functions relative to any anisotropic material symmetry group other than those just mentioned, the widely used isotropic extension method via structural tensors has to result in isotropic extension functions involving at least one structural tensor variable of order higher than two.…”
Section: Methods Of Isotropic Extension As Formulated By Boehler Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides transverse isotropy and orthotropy, Liu’s list includes groups pertaining to crystal classes in the triclinic, monoclinic, and rhombic systems. More recently, Xiao et al [9] demonstrated that “any number of vectors and second order tensors can merely characterize and represent one of the cylindrical groups and the triclinic, monoclinic, rhombic crystal classes.” They proceed to assert what follows:This suggests that, for anisotropic functions relative to any anisotropic material symmetry group other than those just mentioned, the widely used isotropic extension method via structural tensors has to result in isotropic extension functions involving at least one structural tensor variable of order higher than two.…”
Section: Methods Of Isotropic Extension As Formulated By Boehler Anmentioning
confidence: 99%
“…Besides transverse isotropy and orthotropy, Liu's list includes groups pertaining to crystal classes in the triclinic, monoclinic, and rhombic systems. More recently, Xiao et al [9] demonstrated that "any number of vectors and second order tensors can merely characterize and represent one of the cylindrical groups and the triclinic, monoclinic, rhombic crystal classes." They proceed to assert what follows:…”
Section: Qs( V A)qmentioning
confidence: 99%
“…This is E-mail address: marc.francois@u-psud.fr 1 consistent with the Curie principle: the symmetry group of the consequences (the elasticity tensor) includes the symmetry group of the causes (the microstructure). Although informations on microstructure can be described by the use of structure tensors (Xiao et al, 2006), we suppose in this introductory article that the symmetry group of the material is also the symmetry group of the elasticity tensor.…”
Section: Damage Mechanicsmentioning
confidence: 99%
“…It appears possible for many crystalline symmetry groups, although perhaps not all [80], to obtain an isotropic extension w E of Eq. (12) represented by an isotropic function of C and a set of vectors and second-rank tensors designated as structural tensors, which, to be definite, are assumed to be independent of C. To make the point, we focus attention on the special case of a single vector b…”
Section: Frommentioning
confidence: 99%
“…, according to Xiao et al [80]. Degeneracy (confluence of two eigenvalues) in one invariant subspace of A leads once again to transverse isotropy.…”
Section: Frommentioning
confidence: 99%